Mediated Public Diplomacy of the Islamic State in Iraq and Syria: The Synergistic Use of Terrorism, Social Media and Branding - Melki, Jad (2016)
This study aims to provide an initial theoretical model for understanding and analyzing the mediated public diplomacy strategy of virtual states. It examines the mediated public diplomacy strategy of the Islamic State in Iraq and Syria (ISIS) and its ability to synchronize terrorism tactics with communication strategies to gain media access and exposure, push news frames that serve its interests, and target stakeholders with a dual message using sophisticated branding strategies that resonate with cultural values and help it ultimately recruit supporters and deter foes.